THE EFFECT OF USING DIFFERENT CONCENTRATIONS OF TAPIOCA FLOUR ON THE QUALITY OF BARRACUDA FISH CRACKERS (Sphyraena jello) - Vio Gian Wasistha; Slamet Suharto; Ima Wijayanti (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2026)
Barracuda (Sphyraena jello) is a fishery commodity with high potential for value-added processing, including fish crackers. Tapioca flour serves as the primary binding agent, influencing the product's physical, chemical, and sensory qualities. This study aims to evaluate the effect of varying tapioca flour concentrations on the quality of barracuda fish crackers and to determine the optimal formulation. The study was conducted experimentally in a laboratory using a Completely Randomized Design (CRD) with four tapioca flour treatments (0%, 10%, 20%, and 30%) and three replicates. The parameters tested included moisture content, protein, fat, ash, crispness, and sensory evaluation, in accordance with SNI 8646:2018. The results showed that variations in tapioca flour concentration had a significant effect (p<0.05) on all observed parameters. Moisture content ranged from 1.14–1.56%, protein content from 2.51–4.66%, fat content from 21.55–34.50%, ash content from 3.54–7.30%, and crispness from 1112.76–1995.11 gf. Based on the sensory test results, the treatment with 30% tapioca flour addition yielded the highest scores for appearance (8.60 ± 0.81), texture (8.53 ± 0.86), odor (8.27 ± 0.98), and taste (8.80 ± 0.61), with an overall average of 8.55 ± 0.22 (highly preferred category). Thus, a 30% tapioca flour concentration was determined to be the optimal formulation for producing barracuda fish crackers with superior physical, chemical, and sensory quality in accordance with SNI 8646:2018 standards.